A Meta-Analysis of Laninamivir Octanoate for Treatment and Prophylaxis of Influenza. Issue 2 (February 2018) - Higashiguchi, Masayoshi; Matsumoto, Tomoshige; Fujii, Takashi
Background: Laninamivir octanoate is a recently developed inhaled neuraminidase inhibitor for treating influenza virus infection. We performed meta-analyses to clarify the efficacy of laninamivir octanoate on influenza treatment and prevention. Methods: MEDLINE and CENTRAL were searched to identify eligible studies. The log median time to event ratios (logMRs) and log odds ratios (logORs) were combined with meta-analysis. Results: Nine studies in treatment settings and three studies in prophylaxis settings were eligible for this meta-analysis. There was no significant difference between laninamivir octanoate and oseltamivir (8 studies, logMR 0.04, 95% CI [-0.05, 0.14]; P =0.36) or zanamivir (4 studies, logMR -0.01, 95% CI [-0.12, 0.11]; P =0.93) in alleviating fever. However, laninamivir octanoate was associated with significantly longer fever duration in treating H3N2 influenza as compared to oseltamivir (4 studies, logMR 0.29, 95% CI [0.00, 0.59]; P =0.047). Laninamivir octanoate was associated with significantly longer duration of fever as compared to peramivir (4 studies, logMR 0.46, 95% CI [0.14, 0.77]; P =0.004). Laninamivir octanoate significantly reduced the incidence of clinical influenza in post-exposure settings (3 studies, logOR -1.17, 95% CI [-1.72, -0.62]; P <0.001). Conclusions: Overall, the efficacy of laninamivir octanoate in treating influenza was comparable to that of oseltamivir or zanamivir, but it should be noted that laninamivir octanoate was associated with significantly longer fever duration in treating influenza H3N2 as compared to oseltamivir and oseltamivir-resistant mutations in seasonal influenza H1N1 might have affected the results. Peramivir may be superior to laninamivir in treating influenza. Laninamivir octanoate is effective in preventing influenza in post-exposure settings as compared to placebo.